2008
DOI: 10.1590/s0001-37652008000100013
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic nitroxides inhibit the toxicity of nitric oxide-derived oxidants: mechanisms and implications

Abstract: The substantial therapeutic potential of tempol (4-hydroxy-2,2,6,6-tetramethyl-1-piperidinyloxy) and related cyclic nitroxides as antioxidants has stimulated innumerous studies of their reactions with reactive oxygen species. In comparison, reactions of nitroxides with nitric oxide-derived oxidants have been less frequently investigated. Nevertheless, this is relevant because tempol has also been shown to protect animals from injuries associated with inflammatory conditions, which are characterized by the incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
40
0
7

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 35 publications
1
40
0
7
Order By: Relevance
“…(Saito et al, 2003), nitrogen dioxide (NO 2 . ), and the carbonate radical (CO 3 .À ) (Augusto et al, 2008). Tempol readily crosses the BBB (Zhelev et al, 2009), and has previously been shown to provide neuroprotection as a free radical scavenger in several models of brain injury and ischemia (Kwon et al, 2003;Deng-Bryant et al, 2008;Rak et al, 2000;Cuzzocrea et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…(Saito et al, 2003), nitrogen dioxide (NO 2 . ), and the carbonate radical (CO 3 .À ) (Augusto et al, 2008). Tempol readily crosses the BBB (Zhelev et al, 2009), and has previously been shown to provide neuroprotection as a free radical scavenger in several models of brain injury and ischemia (Kwon et al, 2003;Deng-Bryant et al, 2008;Rak et al, 2000;Cuzzocrea et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Cyclic nitroxides are stable free radicals that are potential therapeutic agents because of their pronounced antioxidant properties and low toxicity [1][2][3][4][5][6]. In vivo, the most investigated nitroxide is tempol (4-hydroxy-2,2,6,6-tetramethyl piperidine-1-oxyl), which reduces tissue injury in diverse animal models of oxidative stress and inflammation [7].…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, the routes responsible for transforming NO • into reactive oxidants provide new targets to explore pharmacological interventions aiming to handle the harmful effects of chronic inflammatory conditions. 18,81,82,165 …”
mentioning
confidence: 99%